The Building Site, Redux. Issue 1 (2nd January 2021) - Hyde, Timothy
Abstract : In pursuit of a broader disciplinary understanding of the building site as a social artifact, this experimental seminar undertook the design of prototypical approaches to the representation of historical building sites. To recover the event of building that makes possible, and is superseded by, the built requires novel means of interpreting and representing as a composite whole what existed as a momentary organization of parts. The prototypes described in "The Building Site, Redux" aim to spur new approaches to the building site in architectural education.